Heat Flux of Ionized Layers near the Cathode at Atmospheric Pressure in an Arc Discharge - Saber, Tapark Abdlraheem; Ali, Rafid Abbas; Jawad, Huda Muhammad (Iraqi Journal of Science, 2025)
An arc discharge model for the discharge layers close to the cathode surface is reported. In addition to calculating the degree of plasma ionization and the ionization length to the average free path ratio; the effect of the voltage (U=10 V and 20 V), the temperature of the cathode surface, and mixture concentration (xenon- sodium) on the current density of plasma ( ), of ion ( ji,), of electrons(  ), and of electrons emitted from the surface cathode (jem,) , the ion energy density qi and the electron energy qe was determined. The voltage (U=20V) had a greater effect. At sodium concentrations between (0.1 and 0.5 moles) added to xenon, a shift towards lower temperatures (1500-3000) K after adding sodium concentrations (0.001, 0.01, 0.1 and 0.5) moles to xenon, especially at voltage U=20 V was noted. As a result of the increase in ionization processes, the collision and kinetic energy of electrons have a significant effect on increasing these coefficients at temperatures (3000-5000) K.